1989
DOI: 10.1148/radiology.172.3.2772176
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel phytobezoars: detection with radiography.

Abstract: The authors reviewed the radiographic findings in 19 patients with phytobezoars of the small bowel. The most common predisposing causes were previous gastric outlet surgery and persimmon ingestion. Twelve patients underwent contrast material-enhanced studies of the upper gastrointestinal tract, and one patient underwent a barium enema study. These examinations revealed four gastric, two duodenal, and eight small bowel phytobezoars in 10 patients. The obstruction caused by small bowel phytobezoars frequently oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 0 publications
0
56
0
Order By: Relevance
“…10 Contrast barium studies show an intraluminal filling defect that does not constant fixed to bowel wall. 11 The contrast barium study should be reserved in only partial or intermittent small bowel obstruction. 2 It is useful to use computed tomography for evaluation of small bowel obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…10 Contrast barium studies show an intraluminal filling defect that does not constant fixed to bowel wall. 11 The contrast barium study should be reserved in only partial or intermittent small bowel obstruction. 2 It is useful to use computed tomography for evaluation of small bowel obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this triad has only been useful in accurately diagnosing 10% of preoperative cases. 16,17 On the other hand, Kement et al 13 have reported that abdominal CT was useful for accurate preoperative diagnosis in 77.7% of cases. Furthermore, another report emphasized that CT should be performed in all patients with bowel obstruction to avoid a misdiagnosis and to reduce the use of more invasive treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The typical mottled gas pattern of bezoar is visible in 18 % of patients on plain radiography of the abdomen [8]. The plain radiography can show also the signs of intestinal obstructions whether there are.…”
Section: Discussionmentioning
confidence: 99%
“…Phytobezoars are most common in the elderly patients with inadequate food intake and chronic constipation. Although they represent a rare cause of all intestinal obstructions (0.4-4 %) [8], the most common gastro-intestinal sites are stomach and small intestine, whereas the colon is rarely involved [9][10][11]. We present a rare case of bezoar localized in the cecum tract of the ascending colon in a child with an undefined abdominal pain and no sign of bowel obstruction.…”
Section: Introductionmentioning
confidence: 99%